2018
DOI: 10.3847/1538-4357/aabc13
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Burst Jet Breaks Revisited

Abstract: Gamma-ray Burst (GRB) collimation has been inferred with the observations of achromatic steepening in GRB light curves, known as jet breaks. Identifying a jet break from a GRB afterglow light curve allows a measurement of the jet opening angle and true energetics of GRBs. In this paper, we re-investigate this problem using a large sample of GRBs that have an optical jet break that is consistent with being achromatic in the X-ray band. Our sample includes 99 GRBs from 1997 February to 2015 March that have optic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 173 publications
(239 reference statements)
13
81
0
Order By: Relevance
“…It is possible that currently available datasets (see e.g. Wang et al 2018) do not provide a sufficient number of such GRBs for a p < 0.03 detection of angular jet motions, even if the consequential V − θ c connection exists in nature. However also note, that if in the future, a solid connection between the gamma light curve variabilities (measured from prompt gamma light curves) and the characteristic jet angles (measured from optical afterglows) is found, this could directly provide a method for giving estimates (at least upper limits) on θ c values of GRBs solely from their prompt gamma light curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that currently available datasets (see e.g. Wang et al 2018) do not provide a sufficient number of such GRBs for a p < 0.03 detection of angular jet motions, even if the consequential V − θ c connection exists in nature. However also note, that if in the future, a solid connection between the gamma light curve variabilities (measured from prompt gamma light curves) and the characteristic jet angles (measured from optical afterglows) is found, this could directly provide a method for giving estimates (at least upper limits) on θ c values of GRBs solely from their prompt gamma light curves.…”
Section: Discussionmentioning
confidence: 99%
“…There is a well known standard method for deriving the characteristic angles of GRB jets, θ c , from jet break times of GRB afterglows (see e.g. Wang et al 2018 (Li & Paczyński 2006). Note that both groups of authors assumed that GRB jets are stationary, and that variabilities of GRB light curves are the result of the intrinsic time dependence of the gamma emission process.…”
Section: Measuring Gamma Light Curve Variabilitiesmentioning
confidence: 99%
“…From their sample, 21 overlapped our radio bright sample and 8 overlapped our radio quiet sample. We found the average jet opening angle in the radio loud and quiet sample using the Wang et al (2018) data is < θ j >= 2.6 deg, and < θ j >= 2.04 deg, respectively.…”
Section: Jet Opening Anglesmentioning
confidence: 93%
“…• Finally, we used data from Wang et al (2018), who examined a sample of GRBs that indicated jet breaks in their optical light curves, and that were consistent with an achromatic break in the X-ray light curve at the same time (the achromatic nature of the break is indicative of a physical jet, as opposed to spectral-energy-dependent evolution). From their sample, 21 overlapped our radio bright sample and 8 overlapped our radio quiet sample.…”
Section: Jet Opening Anglesmentioning
confidence: 99%
“…Furthermore, its true kinetic energy E kin,θ = 3.8 +10.2 −2.7 × 10 52 erg is consistent with the energy of the population of supernovae associated with long GRBs 64 . An opening angle of ∼ 1 deg is rarely observed in GRBs 65 and is found in less than 10% of studied populations 66 , which are, however, usually embedded in environments with densities orders of magnitude larger. Extremely narrow opening angles < 1.5 o and jets with steep structure k > 4 are expected in long GRBs due to the initial propagation of the jet into the progenitor material 67,68 .…”
Section: Exceptionally Bright Optical Emission From a Rare And Distant γ−Ray Burstmentioning
confidence: 92%